1978
DOI: 10.3758/bf03199529
|View full text |Cite
|
Sign up to set email alerts
|

Processing of visual illusions in the frequency and spatial domains

Abstract: In the results we report here, complex periodic and aperiodic illusions are revealed by filtering with filters containing one or more straight edges. Positive definite filters are used both in the frequency domain and in the space domain to reveal each illusion. Rotating slit and half-plane filters are used in the frequency domain, while processing is done in the spatial domain by convolution with a rotating slit. These two' schemes show similar results in revealing the illusory patterns. The implications for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Theories that postulate that anomalous contours derive from various forms of local contrast effects which somehow spread across regions that are marked by real edge fragments, line ends, and other features may encounter difficulties in these situations because contrast enhancements of opposite sign, on the one hand, must somehow interact to produce the illusion but, on the other hand, must not simply average out. The opposite-contrast displays also argue against a form of a physiologically based theory (Becker & Knopp, 1978;Ginsburg, 1975), which suggests that anomalous contours are not completely illusory in the sense that they are physically present in the low spatial frequency components of a Fourier transform of the inducing stimuli. Figure 1b illustrates why such an explanation is bound to fail in the displays containing inducing forms of opposite contrast: any (brightness domain) filtering of such stimuli will necessarily produce edges lying perpendicular to the perceived illusory contours.…”
mentioning
confidence: 98%
“…Theories that postulate that anomalous contours derive from various forms of local contrast effects which somehow spread across regions that are marked by real edge fragments, line ends, and other features may encounter difficulties in these situations because contrast enhancements of opposite sign, on the one hand, must somehow interact to produce the illusion but, on the other hand, must not simply average out. The opposite-contrast displays also argue against a form of a physiologically based theory (Becker & Knopp, 1978;Ginsburg, 1975), which suggests that anomalous contours are not completely illusory in the sense that they are physically present in the low spatial frequency components of a Fourier transform of the inducing stimuli. Figure 1b illustrates why such an explanation is bound to fail in the displays containing inducing forms of opposite contrast: any (brightness domain) filtering of such stimuli will necessarily produce edges lying perpendicular to the perceived illusory contours.…”
mentioning
confidence: 98%
“…Ginsburg (1975Ginsburg ( , 1987 and Becker and Knopp (1978) proposed that stimuli inducing illusory contours actually contained the illusory form information in their spatial frequency spectrum-that the illusory forms were not, in fact, illusory if one considered only the low-frequency information ofthe inducer configuration. If the early stages of visual processing had various frequency bands, these low-frequency illusory forms could easily be perceived directly.…”
Section: Spatial Frequency Theoriesmentioning
confidence: 99%
“…Most subjective-contour figures show systematic brightness effects; therefore, the same mechanisms that account for brightness contrast have been used to explain the emergence of these figures (Brigner & Gallagher, 1974;Coren & Theodor, 1977;Day & Jory, 1978Frisby & Clatsworthy, 1975;Jory & Day, 1979). Other investigators have suggested that subjective contours arise from the interactions among the receptive fields of orientation-specific cortical cells (Jung;1973;Jung & Spillman, 1970;Kennedy, 1979;Smith & Over, 1975, 1979 or that they are due to Fourier analysis processes in the visual system (Becker & Knopp, 1978;Ginsburg, 1975). In general, these structural theories have not fared well against recent findings.…”
mentioning
confidence: 99%